2022
DOI: 10.1111/cod.14236
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on skin adverse effects of important hazardous hair cosmetic ingredients with a focus on hairdressers

Abstract: Background: The burden of occupational hand eczema in hairdressers is high, and (partly strong) allergens abound in the hair cosmetic products they use.Objectives: To systematically review published evidence concerning contact allergy to an indicative list of active ingredients of hair cosmetics, namely, p-phenylenediamine (PPD), toluene-2,5-diamine (PTD), persulfates, mostly ammonium persulfate (APS), glyceryl thioglycolate (GMTG), and ammonium thioglycolate (ATG), concerning the prevalence of sensitization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 176 publications
(380 reference statements)
0
7
0
Order By: Relevance
“…Other allergens included thiuram and nickel. Uter et al [9 ▪ ] conducted a systematic review of adverse skin effects of hair cosmetic ingredients that provides detailed information.…”
Section: Database and Registry Resultsmentioning
confidence: 99%
“…Other allergens included thiuram and nickel. Uter et al [9 ▪ ] conducted a systematic review of adverse skin effects of hair cosmetic ingredients that provides detailed information.…”
Section: Database and Registry Resultsmentioning
confidence: 99%
“…A very interesting review of sensitization rates in hairdressers has recently been reported 79 , where PPD showed a high rate, reaching 4.3%. Other relevant haptens such as toluene 2,5-diamine, ammonium persulfate, or glycerin thioglycolate showed global prevalence rates above 1.5%, which is why these allergens are included in the specific hairdressing battery.…”
Section: Occupational Dermatosis: Hairdressingmentioning
confidence: 99%
“…A very interesting review of sensitization rates in hairdressers has recently been published [80]. PPD showed a high prevalence, reaching 4.3% of ACD cases.…”
Section: Occupational Dermatosis: Hairdressingmentioning
confidence: 99%